Association of Fluorescein Angiographic Features with Visual Acuity and with Optical Coherence Tomographic and Stereoscopic Color Fundus Photographic Features of Diabetic Macular Edema in a Randomized Clinical Trial - Danis, Ronald P. (2010)
BACKGROUND: Fluorescein angiography (FA) has been performed as part of the management of diabetic macular edema (DME) for many years. Its current role relative to the role of optical coherence tomography (OCT) is not well defined. PURPOSE: To evaluate the associations of FA features with visual acuity, and with OCT, and fundus photographic characteristics in eyes with DME. METHODS: In a clinical trial, conducted by the Diabetic Retinopathy Clinical Research Network to compare two methods of laser photocoagulation to treat DME, FA (film and digital), color photographs, OCT, and visual acuity measurements were obtained at baseline and at 1 year. Grading of morphologic features was performed at a reading center. Reproducibility of FAs was assessed and the correlations of FA features with visual acuity, OCT, and color photograph features were computed. RESULTS: From 79 clinical sites, data of 323 study eyes and 203 fellow non-study eyes were analyzed. Fluorescein leakage area at baseline was associated with reduced visual acuity, increased OCT measures of retinal thickness and volume, and color photographic measurements of retinal thickening (r = 0.33 – 0.58). No important associations were found with changes from baseline to 12 months in these parameters or with any of the other variables analyzed. CONCLUSIONS: Fluorescein leakage is associated with visual acuity and some OCT and color photographic variables. We did not identify any unique FA variables that had a stronger association with visual acuity than OCT measures of retinal thickness. These data may be useful to investigators planning future DME clinical trials.